Assessment of nutritional status of hemodialysis patients by subjective global assessment score: a single centre study from Karachi, Pakistan - Lubna Ghazi; Dhrolia, Murtaza; Aamna Hamid; Ruqaya Qureshi; Kiran Nasir; Aasim Ahmad (Journal of the Pakistan Medical Association, 2022)
Objective: Despite being an important predictor of morbidity and mortality, routine screening for malnutrition in dialysis patients is not a common practice in Pakistan. Modified Subjective Global Assessment (SGA) is a convenient, inexpensive and practical method to assess nutritional status particularly in resource limited setup. Methods: This cross sectional study was conducted in The Kidney Center Post Graduate Training institute (TKC-PGTI). Patients on maintenance hemodialysis (MHD) were included through non-probability consecutive sampling. A one-time SGA score was calculated based on the history and physical examinations using modified SGA or Dialysis Malnutrition Score (DMS). Chi square test was applied to find association between variables, while to observe the amount of effect of factors on SGA score; binary logistic regression analysis was run. P value of ? 0.05 considered significant. Results: Mild-Moderately malnourished patients were the most frequent in our study 96(64%).None of patient had severe malnourishment. Females were 2.6 times more prone for malnourishment (p value=0.009). More than 5- years on hemodialysis also increased the risk of malnourishment by 12.5 times (p value <0.001). Overweight patients had 85 % less chance of being malnourished as compare to patients with normal weight (p value=0.004). Conclusion: Malnutrition is quite common in hemodialysis patients, which necessitates its regular assessment and monitoring. There is a need to assess the reasons of more malnourishment in female as compared to male. Similarly, the longer duration (> 5 years) on hemodialysis also need attention for prevention and cure of malnourishment. Continuous...